The influence of gender equality-based reproductive health education in increasing sexual knowledge and self-efficacy of adolescent girls - Mustafa, Sri Resky; Nurdiansyah (Innovative Approaches in Health Science Journal, 2024)
Background: Adolescence is a transitional phase connecting childhood and adulthood, requiring special attention and protection. During puberty, adolescents are vulnerable to issues related to reproductive health. This study was conducted at SMP Negeri 1 Bantaeng. Method: The research employed a Quasi-Experimental Pretest-Posttest One Group Design. The population consisted of all second-year female students of SMP Negeri 1 Bantaeng, totaling 67 individuals. The sampling technique used was Total Sampling, where the entire population served as the sample, analyzed using the Paired Sample T-Test. Results: The results showed that among the 67 participants, before being provided with gender-equity-based reproductive health education, 21 students (31.3%) had good knowledge, and 46 students (68.7%) had poor knowledge. After the education, 53 students (79.1%) had good knowledge, and 14 students (20.9%) had poor knowledge. Regarding self-efficacy, before the education, 18 students (26.9%) had high self-efficacy, while 49 students (73.1%) had low self-efficacy. After the education, 44 students (65.7%) had high self-efficacy, and 23 students (34.3%) had low self-efficacy. Conclusion: The findings indicate that gender-equity-based reproductive health education positively influences the improvement of knowledge and sexual self-efficacy among adolescents at SMP Negeri 1 Bantaeng